Handbook on jurisdiction of the Securities and Exchange Commission and other intra-corporate cases - Balbastro, Arturo E. (Rex Book Store, 1992)
Contents: Basic principles and concepts. Selected Supreme Court decisions. Cases where SEC has jurisdiction. Cases where regular courts have jurisdiction. Cases where NLRC has jurisdiction. It is bound to clarify the jurisdictional boundaries and statutory provisions of the Securities and Exchange Commission in relation to the regular courts and the National Labor Relations Commission according to the Supreme Court.